Choukroun’s Autologous Platelet Concentrate Used in Immature Necrotic Tooth during Revascularization: A Clinical and Radiological Report of a Case - Umapathy Thimmegowda; Nagarathna Chikkanarasaiah; Pragna S Vijaya; Pallavi N Kuri; Muhammed T ameem (Journal of South Asian Association of Pediatric Dentistry)
Aim: To discuss the management of an immature necrotic permanent tooth and the clinical and radiological outcome by utilizing platelet-rich fibrin (PRF). Introduction: Traumatic injury to the teeth in children can lead to damage to the pulpal tissue and infection, and particularly in the underdeveloped teeth with immature and open apices, it restricts treatment possibilities. The process of revascularization has enabled increased root survival, symptom relief, and radiographic evidence of root thickening and lengthening with continuous root development. PRF as a scaffold material can be used in a necrotized, infected, immature tooth for regeneration of the pulp and tooth rejuvenation. Case description: This case report displays a protocol of revascularization in which PRF was utilized as an autologous scaffold in an immature necrotized tooth that had undergone trauma with incomplete development of the root. Through examination, clinical, and radiographical investigations, lengthening of the root and thickened dentinal walls of the traumatized tooth were noted.